Timing errors and temporal uncertainty in clinical databases—A narrative review - Goodwin, Andrew J.; Eytan, Danny; Dixon, William; Goodfellow, Sebastian D.; Doherty, Zakary; Greer, Robert W.; McEwan, Alistair; Tracy, Mark; Laussen, Peter C.; Assadi, Azadeh; Mazwi, Mjaye (Frontiers in Digital Health, 2022)
A firm concept of time is essential for establishing causality in a clinical setting. Review of critical incidents and generation of study hypotheses require a robust understanding of the sequence of events but conducting such work can be problematic when timestamps are recorded by independent and unsynchronized clocks. Most clinical models implicitly assume that timestamps have been measured accurately and precisely, but this custom will need to be re-evaluated if our algorithms and models are to make meaningful use of higher frequency physiological data sources. In this narrative review we explore factors that can result in timestamps being erroneously recorded in a clinical setting, with particular focus on systems that may be present in a critical care unit. We discuss how clocks, medical devices, data storage systems, algorithmic effects, human factors, and other external systems may affect the accuracy and precision of recorded timestamps. The concept of temporal uncertainty is introduced, and a holistic approach to timing accuracy, precision and uncertainty is proposed. This quantitative approach to modelling temporal uncertainty provides a basis to achieve enhanced model generalizability and improved analytical outcomes.